2023
DOI: 10.1177/00034894231158464
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Metastases in Papillary Thyroid Carcinoma can be Predicted by a Convolutional Neural Network: a Multi-Institution Study

Abstract: Objectives: The presence of nodal metastases in patients with papillary thyroid carcinoma (PTC) has both staging and treatment implications. However, lymph nodes are often not removed during thyroidectomy. Prior work has demonstrated the capability of artificial intelligence (AI) to predict the presence of nodal metastases in PTC based on the primary tumor histopathology alone. This study aimed to replicate these results with multi-institutional data. Methods: Cases of conventional PTC were identified from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…The best-performing institution's combined algorithm had a sensitivity and specificity of 68% and 91%, respectively. The authors concluded that the results were comparable to the ones obtained in their previous study, confirming the future potential advantage of using AI technologies to generate algorithms able to predict the presence of lymph node metastases in patients with PTC [87] .…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The best-performing institution's combined algorithm had a sensitivity and specificity of 68% and 91%, respectively. The authors concluded that the results were comparable to the ones obtained in their previous study, confirming the future potential advantage of using AI technologies to generate algorithms able to predict the presence of lymph node metastases in patients with PTC [87] .…”
Section: Resultssupporting
confidence: 77%
“…Recently, the same authors conducted a follow-on multicenter study aimed at further assessing the ability of a CNN to predict the presence or absence of lymph node metastases in patients with PTC [87] . When CNN from one institution was tested against images from the other institution, the achieved sensitivity and specificity were 65% and 61%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Anand et al 2021 described a weakly supervised technique to train a DNN (deep neural network) to predict BRAF V600E mutational status with high accuracy, in unannotated H&E-stained images of thyroid cancer tissue (12). Two studies by Esce et al 2021 & 2023 demonstrated the efficacy of CNN in predicting the probability of nodal metastases in PTC (papillary thyroid carcinoma) based on the histopathology features of the primary tumor (13, 14). Finally, a study by Nojima et al 2023 compared the prediction accuracy of 3 CNN models in distinguishing FA (follicular adenoma) from FTC (follicular thyroid carcinoma) based on histopathology images (15).…”
Section: Resultsmentioning
confidence: 99%
“…These included a study by Anand et al 2021 ( 12 ) that described a weakly supervised technique to train a DNN (deep neural network) to predict BRAF V600E mutational status with high accuracy in unannotated H&E-stained images of thyroid cancer tissue. Two studies by Esce et al ( 13 , 14 ) demonstrated the efficacy of CNNs in predicting the probability of nodal metastases in PTC (papillary thyroid carcinoma) based on the histopathology features of the primary tumor. Finally, a study by Nojima et al 2023 ( 15 ) compared the prediction accuracy of 3 CNN models in distinguishing FA (follicular adenoma) from FTC (follicular thyroid carcinoma) based on histopathology images.…”
Section: Resultsmentioning
confidence: 99%